A study of awareness level on building surveying profession among professionals in construction industries / Siti Mulaikah Batul Abdul Muttalib - Siti Mulaikah Batul Abdul Muttalib (Faculty of Architecture, Planning and Surveying, 2013)
Building Surveyor plays an important role in Construction Industry. Nowadays, Building Construction demand have increased more and more but in the same time the incidents of building collapsed also increased coherently. Due to the damage and fault of design found, people started to seek for another to be blamed of rather than to investigate the factor that contributes towards incidents. This is about the Building Surveyor roles and responsibilities. The kick start of Building Surveyor has begun to develop and people are still blurred and looking towards other professionals in this country. So, this study has been carried out to determine the level awareness among construction industry professionals towards Building Surveying profession in Malaysia. The objectives are to study on Building Surveying Profession in Malaysia, to investigate the level of awareness among Construction Industry Professionals towards Building Surveying Profession establishment and also to recommend way to create awareness on the importance of Building Surveying Profession. The respondents are the Construction Industry Professionals. The paper presents the analysis awareness level of Building Construction Professionals towards Building Surveyor’s profession recognition and Building Surveyor’s establishment.